Influence of ski boots on balance performance and intermuscular coordination - Mildner, E.; Raschner, C.; Lembert, S.; Patterson, C.; Märzendorfer, P. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The development of carving skis and carving technique in alpine skiing has increased the importance of balance and proprioception training for skiers. Noé & Paillard (2005) compared national to regional ski racers in an unstable position with or without ski boots. The 2 groups had similar results with ski boots, but the national skiers were worse without ski boots. This might be a long term effect of repetitive wearing of ski boots. The aim of this study was to analyse the influence of ski boots on a) balance performance of alpine skiers with different skill levels and b) intermuscular coordination differences.